THE EFFECT OF BABY SPA (BABY MASSAGE, BABY SWIM, AND BABY GYM) ON THE QUALITY OF SLEEP AND GROWTH OF BABIES AGED 0-6 MONTHS - Hendriyani, Feftin (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2023)
Abstract Background: The most rapid development of babies occurs during the golden age so stimulation becomes very important in the process of growth and development. At this time, if stimulation factors are not provided enough, the child will experience problems with sleep quality and growth, such as weight gain and gross motor skills. This research aims to explain the effect of baby SPA (baby massage, baby swim, and baby gym) on sleep quality and growth and development (weight and gross motor skills) of babies aged 0-6 months. Method: A literature review was carried out through searching for relevant articles from electronic databases (Scient Direction, Pubmed, Google Scholar,) using the following keywords: